IMPLEMENTASI PERATURAN MENTERI NO 3 TAHUN 2015 TENTANG PENDAMPING DESA DI KECAMATAN SUNGAI AMBAWANG - Syamsuddin, Syamsuddin; Martoyo, Martoyo; Hutomo, Tri (PublikA Jurnal Ilmu Administrasi Negara (e-Journal), 2023)
This research aimed to analyze the Implementation Process of Ministerial Regulation no. 3 of 2015 concerning Village Assistant in Pasak Village and Pasak Piang Village, Sungai Ambawang Sub-District. The method used in this research was a qualitative descriptive research type. According to Van Metter and Van Horn in Agustino (2008:142) that the most important variables for the success of the policy implementation process are: 1) Policy Size and Objectives: village local facilitators have responsibilities in village development 2) Resources: the conclusion is that Sungai Ambawang Sub-district does not yet have adequate human resources for the PD Program (Village Facilitator) in implementing this PD (Village Facilitator), Based on the provisions issued by the ministry in Sungai Ambawang Sub-district should have four or five assistants in the process of implementing PD (Village Facilitator) in the field. 3) Characteristics of Implementing Agents: the conclusion is that the results of the work or achievements carried out by our Village Facilitators will be able to analyze and evaluate objectively to carry out village development through empowerment of the community. 4) Attitudes/Tendencies of Implementers: the conclusion is that the commitment and attitude of village facilitators based on several coaching and empowerment activities carried out by Pasak and Pasak Piang Village Facilitators as mentioned above when analyzed are indeed in accordance with what is mandated in the Government Regulation of the Republic of Indonesia No. 47 of 2015.Â Â Keywords: Implementation, Policy, Village Assistant, Sungai Ambawang Sub-District.